2013
DOI: 10.3346/jkms.2013.28.5.763
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Korean Version of the Internet Addiction Test among College Students

Abstract: We developed a Korean translation of the Internet Addiction Test (KIAT), widely used self-report for internet addiction and tested its reliability and validity in a sample of college students. Two hundred seventy-nine college students at a national university completed the KIAT. Internal consistency and two week test-retest reliability were calculated from the data, and principal component factor analysis was conducted. Participants also completed the Internet Addiction Diagnostic Questionnaire (IADQ), the Kor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 26 publications
4
81
0
2
Order By: Relevance
“…Our data confirm internal consistencies of the CIUS and the IAT that had been suggested by previous studies [11,23,24,25,26,27]. Low Cronbach's α scores were found for IAT subscales ‘Neglect of work', ‘Anticipation' and ‘Neglect of social life'.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our data confirm internal consistencies of the CIUS and the IAT that had been suggested by previous studies [11,23,24,25,26,27]. Low Cronbach's α scores were found for IAT subscales ‘Neglect of work', ‘Anticipation' and ‘Neglect of social life'.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, it is necessary to investigate in detail whether or not the present cut-offs represent a threshold with respect to clinical relevance and impairment. Further limitations of our study include that in contrast to the six-factor structure we used for our analysis within subscales [27], more recent studies found strongly varying factor solutions for the IAT [23,26,43]. This discrepancy should be topic of future research.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…On the one hand, the term ''addiction'' has been repeatedly criticized (Pezoa-Jares, EspinozaLuna, & Vasquez-Medina, 2012;Rehbein & Möble, 2013), allowing the emergence of new terminologies less controversial such as problematic, pathological, excessive or compulsive Internet use, all describing the same phenomenon (Adièle & Olatokun, 2014;Lee et al, 2013). Among these terms, Problematic Internet Use (PIU) seems to be the most popular (Hsu & Shih, 2013) and thus will be primarily used in this article.…”
Section: Introductionmentioning
confidence: 98%
“…Caplan (2002) demonstrou existir uma associação entre o uso problemático da Internet e a depressão, assim como outros estudos (Kraut, et al, 1998;Lee, Lee, Gyeong, Yu, Song, & Kim, 2013).…”
unclassified